Macroeconomic Market Incentive Plans: History and Theoretical Rationale - Kenneth Koford; Jeffrey B. Miller (Levy Economics Institute of Bard College, 1992)
This paper explores the contemporary debate among economists on the means to move the economy toward high employment without inflation-beyond the traditional instruments of monetary and fiscal policy. The authors pay particular attention to the Market Anti-Inflation Plan (MAP), submitted by Lerner and Colander in 1980. The reasons economists have searched for alternative measures relate to the problems associated with wage and price controls. MAP is an anti-inflation plan that allows relative prices to adjust: The scheme increases costs to firms that raise prices, and contains an added incentive to lower prices. Since MAP is designed to fight macroeconomic inflation by changing the incentives of individual price setters, the relationship between microeconomic behavior and macroeconomic outcomes must be addressed. The theoretical justification for MAP is that there is a macroeconomic externality, and MAP can mitigate the ramifications of the externality. However, efforts to more clearly define the nature of this externality require a better understanding of transaction costs. Consequently, there will be the need for a mechanism to integrate such costs into microeconomic and macroeconomic models.
Keywords: 330